Drivers of cardiovascular disease in metabolic dysfunction-associated steatotic liver disease: the threats of oxidative stress - Minetti, Erika T.; Hamburg, Naomi M.; Matsui, Reiko (Frontiers in Cardiovascular Medicine, 2024)
Non-alcoholic fatty liver disease (NAFLD), now known as metabolic-associated steatotic liver disease (MASLD), is the most common liver disease worldwide, with a prevalence of 38%. In these patients, cardiovascular disease (CVD) is the number one cause of mortality rather than liver disease. Liver abnormalities per se due to MASLD contribute to risk factors such as dyslipidemia and obesity and increase CVD incidents. In this review we discuss hepatic pathophysiological changes the liver of MASLD leading to cardiovascular risks, including liver sinusoidal endothelial cells, insulin resistance, and oxidative stress with a focus on glutathione metabolism and function. In an era where there is an increasingly robust recognition of what causes CVD, such as the factors included by the American Heart Association in the recently developed PREVENT equation, the inclusion of liver disease may open doors to how we approach treatment for MASLD patients who are at risk of CVD.